2020
DOI: 10.1097/brs.0000000000003215
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Lengthening With Magnetically Controlled Growing Rods

Abstract: Study Design. Laboratory analysis of explanted MAGnetic Expansion Control (MAGEC) rods. Objective. The aim of this study was to identify the in vivo lengthening of MAGEC rods. Summary of Background Data. Little data is available regarding the lengthening achieved by MAGEC rods. Methods. Cases were identified from the largest series of independently analyzed expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 35 publications
0
31
1
Order By: Relevance
“…This is in contrast to MCGR, where failure to distract is common due to component failure of the driving mechanism. [15][16][17]34,40] Strengths of the current study include the relatively large patient cohort that was prospectively followed for at least 2 years. In addition, the diverse patient group represents a varied EOS population, as observed by the considerable variation in baseline EOSQ-24 domain scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to MCGR, where failure to distract is common due to component failure of the driving mechanism. [15][16][17]34,40] Strengths of the current study include the relatively large patient cohort that was prospectively followed for at least 2 years. In addition, the diverse patient group represents a varied EOS population, as observed by the considerable variation in baseline EOSQ-24 domain scores.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that less than 1 in 5 retrieved MCGRs still function as intended. [15][16][17] It is also an expensive device, precluding its use in large parts of the world. To address these drawbacks, we developed the Spring Distraction System (SDS), which employs the continuous distraction force of a compressed helical coil spring that is positioned around a standard rod that is allowed to slide at the proximal-or distal foundation ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Further detailed analysis of the mechanism of failure of MAGEC rods and associated metallosis has been reported in studies by Joyce et al 23 and Rushton et al 49,50 as part of a UK retrieval analysis project. In a first report of 34 explanted MAGEC rods, abrasive marks on the extending bar and internal titanium wear debris were identified in all explants.…”
Section: Implant Failurementioning
confidence: 95%
“…In a further study, Rushton et al 50 assessed the capacity of explanted MAGEC rods to still generate force compared to their intended pre-implantation standard. A bespoke force gauge provided by the MAGEC manufacturer was used to test 45 explants from 25 patients; the majority of these were Modification 2 MAGEC rods.…”
Section: Implant Failurementioning
confidence: 99%
See 1 more Smart Citation